Exploring the Role of Insulin Resistance in Hormonal imbalance in PCOS patients: Menjelajahi Peran Resistensi Insulin dalam Ketidakseimbangan Hormon pada Pasien PCOS - Nabil Hamdullah Al-Fahadi; Aya dhaher J; Astbraq Haitham A.; Sidra Yassin H. (Academia Open, 2025)
General Background: Urinary tract infections (UTIs) are a significant concern for transfusion-dependent beta-thalassemia (TDT) patients due to their compromised immune systems and frequent hospital visits. Specific Background: Identifying virulence factor genes in bacterial species isolated from UTIs in TDT patients is crucial for understanding pathogenicity and improving treatment strategies. Knowledge Gap: Despite the high prevalence of UTIs in TDT patients, limited studies have focused on detecting virulence factor genes in the bacterial isolates from this specific population. Aims: This study aims to identify virulence factor genes in bacteria isolated from the urine samples of TDT patients with UTIs. Results: Among 173 urine samples, bacterial growth was observed in 38 samples (21.96%), while 135 samples (79.03%) showed no growth. The identified isolates included Escherichia coli, Enterobacter cloacae, and Klebsiella pneumoniae, confirmed through DNA extraction, universal primers, and partial 16S rRNA sequencing. Novelty: This study provides new insights into the molecular characteristics of bacterial pathogens in TDT patients, highlighting the presence of specific virulence factors that contribute to infection severity. Implications: The findings enhance our understanding of bacterial virulence in TDT-related UTIs, offering a foundation for targeted therapeutic strategies and improved clinical management. Highlights: UTI Risk: TDT patients have higher susceptibility due to immune dysfunction. Bacterial Profile: E. coli, E. cloacae, and K. pneumoniae dominate infections. Clinical Impact: Supports targeted therapy for managing UTIs in TDT patients. Keywords: Urinary Tract Infection, Beta-Thalassemia, Virulence Factors, Bacterial Pathogens, 16S rRNA Sequencing